Acute Appendicitis as the Initial Presentation of Kawasaki Disease Shock Syndrome in Children - Yuan-Hao Chang; Chien-Yu Lin; Lu-Hang Liu; Fu-Huan Huang; Yu-Jyun Cheng (MDPI AG, 2022)
Kawasaki disease shock syndrome (KDSS) is a severe form of Kawasaki disease (KD). The hemodynamic instability and atypical manifestations of this syndrome delay its correct diagnosis and timely treatment. We report here an eight-year-old girl who presented with appendicitis. Her fever persisted after appendectomy, accompanied by hemodynamic instability. The girl was diagnosed with KDSS. Intravenous immunoglobulin (IVIG) and corticosteroids were administered. Her symptoms resolved. She had left coronary artery dilatation, which resolved three months later. We also reviewed two other possible cases identified as KDSS with appendicitis. These cases have a more atypical clinical course, prolonged treatment, and a higher rate of IVIG resistance. Better awareness of KDSS is needed for early diagnosis and treatment in children experiencing prolonged fever after appendectomy.